Pain management & opioid dose reduction with topical sevoflurane instillations in intractable venous ulcers: a case report - F. Dámaso Fernández-Ginés; Manuel Cortiñas-Saenz; Desirée Agudo-Ponce; José Antonio Morales-Molina; Carmen Fernández Sánchez; Francisco Sierra-Garcia (Universidade de São Paulo, 2022)
Abstract Vascular ulcers (VU) constitute a major cause of pain and disability, and significantly compromise quality of life. VU have a natural tendency to become chronic and in many cases exhibit anunsatisfactoryresponse to many of the standard therapeutic options.The case of a 73 year-old Caucasian female with severe pain and poorly-controlled pain (Visual Analogic Scale-VAS- of 8-9) due to three lower leg long-standing VUs is reported and discussed herein. The patient was treated with topical instillations of undiluted sevoflurane as per institutional off-label protocol (starting doses of 1mL/cm2 twice a day, and up-titrated according to response to a maximum of 7 mL twice daily). The VAS score dropped to 0-1 shortly after initiation of therapy and remained stable throughout treatment up until the closure of the observations. Subsequently, opioid therapy was gradually tapered down and ultimately abandoned.Sevoflurane application resulted on adequate and sustained pain management of refractory VU, with no significant side effects. On account of its beneficial effectivity and safety profiles, topical sevoflurane emerges as an add-on alternative for the long-term management of VU, and potentially other painful conditions.